Evaluation of factors militating against quality assessment in Oyo State, Nigeria (2020)
A critical aspect of education is assessment. There are diverse reasons for the essence of assessment in schools; however, so many problems affect qualitative assessment in Nigeria today. This study, therefore, examined the challenges of quality assessment among teachers in Oyo State, Nigeria. Some of these challenges faced by the teacher in Oyo state in conducting quality assessment include teachers' poor perception of assessment, poor competences to carry out an assessment, excessive use of summative assessment more than formative assessment, lack of resources, socio-cultural problems and lack of technical know-how. Based on these findings it was concluded that quality assessment for sustainable development among teachers in Oyo state faces a lot of challenges. Therefore, teachers should be trained on development and utilization of tests, the government should enhance teacher education with the infusion of information technology in training teachers at all level on the job training and in-service program on Educational Test and Measurement. This will go a long way to influence teachers' attitudes towards quality assessment. Qualified teachers should be employed to help in strengthening students' assessment.